Asociación entre inadecuada ganancia de peso según hábito corporal en gestantes a término y complicaciones maternas. Instituto Nacional materno Perinatal. 2006-2009 - Mejia Álvarez, Christian Richard Carlos (2010)
Introduction: Its well known that gain of maternal weight will influence in the gestation and in the new one, but, in our medium this only is taken as another control, what generates that don’t give the importance that really deserves; in spite of the fact that in other countries this is used for the prevention of neonatal and maternal risks to short and long time limit. Material and Methods: With a historic cohort it was a matter of determining if there existed association among the inadequate increase of weight during the gestation and the maternal complications, in the Perinatal Maternal Institute, 2006-2009. It has worked with a level of statistical significance p<0,05. Obtaining the relative Risks (RR) according to maternal IMC. The statistical program was utilized STATA ® version 10,0. Results: More than 27000 patients were studied to determine that, according to the IMC pre gestacional, if pregnant women increases less than 13,5 Kg. (<20), less than 11,5 Kg. (20-25) and less than 9 Kg. (>25), they have an increment of 2,14; 1,25 and 1,16 times in their RR (respectively) to present a complication. There were found statistical significances in the variables: tear during the moment of the labor, the urinary infection post labor, the infection of the operating injury, culmination of the pregnancy by cesarean section, the gestational hypertensive, the presentation of anemia, the obtaining of a large product and the fetal suffering intra uterus. Discussions and conclusions: Exists association among the inadequate gain of weight according to corporal habit in pregnant women to term and maternal complications.